2016
DOI: 10.1177/1687814016674697
|View full text |Cite
|
Sign up to set email alerts
|

Developing the process in matching a wind turbine system to attain optimal performance

Abstract: The objective of this article is to develop the procedure in the matching of turbine blades and generator to increase the efficiency of a wind turbine. Hydrodynamic simulation of turbine blades and the logic setting of the controller are always focused on obtaining maximum power from the turbine system. Research on the matching of the two systems, turbine blades and the generator, is rare. If turbine blades are not initially well matched with the generator, the optimal design of the turbine blades to reach pea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…If designers can quickly find a wind rotor and a generator with matching performance in existing products so as to quickly build a wind power system and analyze and forecast its performance, it will greatly improve the design efficiency and reduce the design cost for a wind power system. However, studies on the matching of the wind turbine and generator are rare and the matching problem is worthy of being discussed [5]. Therefore, it is a key problem to explore the analytical methods of the overall output model of a wind power system and the performance matching between components.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…If designers can quickly find a wind rotor and a generator with matching performance in existing products so as to quickly build a wind power system and analyze and forecast its performance, it will greatly improve the design efficiency and reduce the design cost for a wind power system. However, studies on the matching of the wind turbine and generator are rare and the matching problem is worthy of being discussed [5]. Therefore, it is a key problem to explore the analytical methods of the overall output model of a wind power system and the performance matching between components.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of Vlad et al showed that the overall efficiency of low power wind turbines was closely related to generator performance, electrical power optimization and mechanical performance optimization [20]. Kao proposed to develop a matching program between wind turbine blades and generators to improve the efficiency of wind power systems by determining the optimal constant pressure mode for generators [5]. These studies provide ideas and referential methods for component modeling.…”
Section: Introductionmentioning
confidence: 99%